Potential vectors of equine arboviruses in the UK. (7th January 2017) - Chapman, G. E.; Archer, D.; Torr, S.; Solomon, T.; Baylis, M.
Abstract : There is growing concern about the increasing risk of disease outbreaks caused by arthropod‐borne viruses (arboviruses) in both human beings and animals. There are several mosquito‐borne viral diseases that cause varying levels of morbidity and mortality in horses and that can have substantial welfare and economic ramifications. While none has been recorded in the UK, vector species for some of these viruses are present, suggesting that UK equines may be at risk. The authors undertook, therefore, the first study of mosquito species on equine premises in the UK. Mosquito magnet traps and red‐box traps were used to sample adults, and larvae were collected from water sources such as tyres, buckets, ditches and pools. Several species that are known to be capable of transmitting important equine infectious arboviruses were trapped. The most abundant, with a maximum catch of 173 in 72 hours, was Ochlerotatus detritus, a competent vector of some flaviviruses; the highest densities were found near saltmarsh habitats. The most widespread species, recorded at >75 per cent of sites, was Culiseta annulata. This study demonstrates that potential mosquito vectors of arboviruses, including those known to be capable of infecting horses, are present and may be abundant on equine premises in the UK.